Utilização da casca de arroz como adsorvente para corantes, fármacos, metais e óleos: revisão e aspectos recentes - COELHO, Heloisa Heidtman da Silva (2022)
One of the main problems related to water is contamination, which can change its physical, chemical and biological properties. One can mention as contaminants dyes, metals, drugs and oils in their various variations. Conventional effluent agreements are expensive and that is why alternative means of treatment are increasingly sought, such as the use of rice husk as an adsorbent. This work aimed to develop a descriptive bibliographic review of research carried out with rice husk as an adsorbent material in the four contaminants. For this, the methodology was divided into three main stages: definition of the object of study, in-depth research on the object of study and analysis of the results. Based on the information, it was noticed that rice husks can undergo physical, chemical and biological treatment. These treatments can improve the ability to remove contaminants. In some cases, adsorption increased from 24.55% to 93.51% after shell modification. Parameters such as pH, contact time, temperature, initial amount of adsorbate are directly related to the adsorptive process, which can improve or worsen the results. In one study, the removal efficiency dropped from 60.93% to 34.40% due to the initial dye concentration; while in another, an adsorption increased from 80.00% to 90.00% due to a variation in contact time. According to the consulted references, the residue demonstrates relevant results in different types of dyes, drugs, metals and oils, reaching satisfactory results and as removal efficiencies in most cases. Furthermore, it is possible to recover the adsorbent and the adsorbate through the desorption process. It is recommended that more studies be carried out involving a rice husk, so that its functionalities and varieties are even better understood. One can also look for other natural-based adsorbents to replace it.